Profile of Meningioma Patients at Dr. Soetomo General Academic Hospital - Valeryna, Natasha; Ardiansyah, Djohan; Susanto, Joni; Utomo, Sri Andreani (Universitas Airlangga, 2024)
Highlight: Meningioma, the most common primary brain tumor, is typically found in women aged 40-49 years old. Meningiomas can show distinctive characteristics on clinical, radiological, and histopathological examinations. There were significant differences in histopathological grading between male and female patients, as well as between homogenous and heterogenous contrast enhancement. ABSTRACT Introduction: Meningioma is an intracranial extracranial tumor that arises from arachnoid cells. It is reported to be the most common primary brain tumor (39%). Meningioma is diagnosed based on clinical and radiological findings, but a definitive diagnosis requires histopathology examination. However, the clinical, radiological, and histopathological profile of meningioma is rarely studied in Indonesia. Objective: This study aimed to identify the clinical, radiological, and histopathological profile of meningioma patients at Dr. Soetomo General Academic Hospital Surabaya from 2017 to 2021. Methods: This was a retrospective observational study with a cross-sectional design using secondary data collected from electronic medical records at Dr. Soetomo General Academic Hospital Surabaya in 2017-2021. Results: A total of 256 patients were included in this study. The majority of the patients in this study were female (83.98%), aged 40-49 years old (43.36%), and mostly had the clinical symptom of headache (35.94%). Meningiomas were mostly WHO grade I (85.16%), with a transitional subtype (44.92). Based on the Kruskal-Wallis test, there were differences in histopathological grading between male and female patients (p = 0.000), as well as between homogenous and heterogenous tumor enhancement (p = 0.027). However, there were no differences in histopathological grading between the dural tail findings (p = 0.181) and hyperostosis findings (p = 0.135). Conclusion: Meningioma was found to be more common in females than in males, with the peak occurring in 40-49 years old. The most prevalent clinical symptom was headache, and convexity was the most common location for these tumors, most of which were larger than 3 cm. The majority of meningiomas were WHO grade I with transitional subtype.